Climate changing and critical environmental education in a public school contexto through biology teaching - Inez da Silva, Karen Luana; Silva Maia, Jorge Sobral da [UNESP] (Federal Univ Rio Grande, Inst Education, 2023)
This article discusses the challenges and perspectives existing in biology teaching in public school context, when talking about climate changing, based on Critical Environmental Education (EAC) which is reason edon the theoretical-methodological assumptions in Historical-CriticalPedagogy (PHC) and historical-dialectical materialism. By monitoring the teaching process, with a semi-structured interview of biology teacher, this article discusses the complexity in a relation between climate change and public education in general, and the biology teaching specifically. The thoughts brough there are articulated with the possibilities that biology teaching introduces, with the contribution to the debate related to climate emergency, if guided by a pedagogical theory that aims the historical-critical foundations appropriation for social transformation, beyond the conservatism and reductionism existing in this discussions involving the socio-environmental issue in Brazil. Keywords: Historical-CriticalPedagogy, schoolpraxis, socio-environmental crisis.
Keywords: Historical-CriticalPedagogy; schoolpraxis; socio-environmental crisis.